2009
DOI: 10.1002/ppp.640
|View full text |Cite
|
Sign up to set email alerts
|

The influence of seasonal climatic parameters on the permafrost thermal regime, West Siberia, Russia

Abstract: Statistical correlations between seasonal air temperatures and snow depths and active layer depths and permafrost temperatures were analysed for tundra (Marre‐Salle) and northern taiga (Nadym) sites in Western Siberia. Interannual variations in active layer depth in the tundra zone correlated with the average air temperature of the current summer, and in peatland and humid tundra, also with summer temperatures of the preceding 1–2 years. In the northern taiga zone, the active layer depth related to current sum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…The investigated parameters include MAAT, mean summer temperature, mean winter temperature, annual TDD and winter season FDD, summer precipitation and snow depth/winter precipitation. For all parameters, the regression analyses were performed for the same year and for the preceding year, because Popova and Schmakin () found the best correlation with active‐layer depths in tundra peatlands with summer air temperatures of the preceding 1–2 years. The regressions were considered statistically significant if p ≤ 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The investigated parameters include MAAT, mean summer temperature, mean winter temperature, annual TDD and winter season FDD, summer precipitation and snow depth/winter precipitation. For all parameters, the regression analyses were performed for the same year and for the preceding year, because Popova and Schmakin () found the best correlation with active‐layer depths in tundra peatlands with summer air temperatures of the preceding 1–2 years. The regressions were considered statistically significant if p ≤ 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have explored the influence of meteorological parameters on the thermal regime in peatlands. In West Siberian tundra peatlands, Popova and Schmakin () concluded that seasonal air temperatures explain more of the active‐layer depth variability than do mean annual air temperature (MAAT) and annual thawing degree‐days (TDD – the cumulative sum of mean daily air temperatures for days when temperatures are above 0 °C) or freezing degree‐days (FDD – the cumulative sum of mean daily air temperatures for days when temperatures are below 0 °C). These authors found that summer air temperatures of the preceding 1–2 years have the greatest impact on active‐layer depths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing active-layer thicknesses over the past few decades have been reported from elsewhere in the Arctic, including Russia (Mazhitova et al, 2004;Popova and Shmakin, 2009), Iceland (Kneisel et al, 2007), Sweden (Akerman and Johansson, 2008), and North America (Zhang and Stamnes, 1998;Osterkamp, 2005;Burn and Kokelj, 2009). Notably, since 1950, the Arctic Oscillation has shown a statistically significant trend towards a positive phase (Balzter et al, 2007), which is thought to indicate global climate change.…”
Section: The Third Period From 1960 To the Presentmentioning
confidence: 89%
“…; numerous rivers have incised the coastal plain to depths of 15 m a.s.l. Massive ground ice bodies, which are believed to have an origin either as segregated ice or glacier ice (Trofimov et al, 1975;Astakhov, 2006), have been significantly affected by thermokarst processes due to human impact and global warming (Popova and Shmakin, 2009). The mean annual air temperature (MAAT) over Russia has risen by $18C in the last 20 years (Shmakin and Popova, 2006).…”
Section: Field Areamentioning
confidence: 99%